Evasão e ações de permanência e êxito na educação profissional técnica de nível médio na modalidade subsequente: o caso do Instituto Federal do Amazonas - Campus Avançado Manacapuru - Silva, Jeane de Lima (2021)
The present work presents the results of a research that aimed to investigate the factors that have led students to drop out of school from the subsequent modality of the Advanced Campus Manacapuru and what educational product could be developed in order to contribute to the permanence and success of the students. The topic is being discussed since the developments that accompany the expansion of the EPT Network (Professional and Technological Education), including the dropout and retention rates. This work assumes that the measures to be adopted to ensure the completion of subsequent technical courses need to consider the specifics of each regional context and the profiles of the subjects served - that is why the analysis of the specific case in the Advanced Campus Manacapuru belonging to the Federal Network of Education, located in the State of Amazonas, 80 kilometers from the capital Manaus. Fifteen dropout students, 05 professors, 05 technical-administrative servers and the campus manager participated in the research. To develop the research, we used the case study method because it allows to investigate a contemporary phenomenon within its real context, in this case the investigated campus. The research results, based on the data analysis spiral proposed by Creswel (2014), pointed out that the factors that have led students from the subsequent modality of the Manacapuru Advanced Campus to dropout are: attending higher education; the feeling of discouragement with the course, due to different aspects, and financial difficulties for not having a professional occupation; sick leave and new job; insecurity and personal difficulties; lack of identification with the area; lack of flexibility in working hours; learning difficulties. In view of these factors, an educational product was created, entitled Operational Protocol for Permanence and Success - POPE, which aims to contribute to the permanence and success of students. This product was evaluated by twelve members of the research group and by an ad hoc committee composed of five social workers from the IFAM countryside campuses.